seQuRe: an Integrated Dual Digital QR and Invisible Watermark - P. Assiroj; B. Hartati; Sohirin Sohirin; B. Mulyawan; R. K. Astuti; I.A Prabadhi; C. Trinata; G.B Hertantyo; C. Susaningsih; M.F. Romdendine; O.P Martadireja (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study introduces seQuRe, a novel approach that employs a dual-layer QR code system combined with invisible watermarking to enhance security measures in data transmission. The outer layer of the QR code facilitates general data accessibility while the inner layer, encrypted and embedded within the outer, secures sensitive information accessible only through specialized scanning. Utilizing advanced encryption standards (AES), this system ensures data integrity and confidentiality. The invisible watermarking further augments security by embedding additional data that verifies authenticity. Through systematic experimentation using Python and various libraries on Google Colaboratory, this experiment demonstrates the efficacy of seQuRe in resisting common cyber-attacks while maintaining data fidelity. We measured the peak-signal-to noise-ratio (PSNR) and the normalized cross-correlation (NCC) values of the QR images into which we had embedded watermarks, obtaining a PSNR value of 57.53 and an NCC value of 0.999. Subsequently, we also conducted simulation of attacks on the watermarked QR code with salt and pepper noise, speckle noise, and Gaussian noise attacks. From these attacks, we obtained PSNR values of 54.24 and NCC values of 0.6699 for the salt and pepper noise attack, 50.837 and 0.7319 for the speckle noise attack, and 33.17 and 0.0941 for the gaussian noise attack. The result underscores its potential application across industries requiring secure data handling and transmission. The implementation of such technology promises significant improvements in digital security, aiming to keep pace with the evolving landscape of cyber threats.